STRATEGI PENGELOLAAN SAMPAH PADA BANK SAMPAH INDUK SURAKARTA: KAJIAN PERSPEKTIF GERAKAN SOSIAL BARU - Hidayatunnisa, Faradina; Yosafat Hermawan Trinugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The increasing amount of waste generation in Surakarta City demands an effective waste management strategy based on community participation. The Central Waste Bank of Surakarta (BSI) serves as a solution to reduce the volume of waste entering the Final Disposal Site (TPA) while fostering environmental awareness within the community. This study aims to analyze the strategies implemented by Bank Sampah Induk Surakarta in mobilizing community participation in waste management and its relation to the concept of the New Social Movement. This research employs a qualitative approach with a descriptive method. The use of a descriptive method aims to provide a clear and in-depth depiction of the strategic processes applied by BSI in encouraging community participation in waste management. The results of the study indicate that the strategies implemented by BSI include education and outreach on waste separation, the provision of adequate facilities, ease of operational access, and community involvement in involvement in sustainable programs. These strategies align with the characteristics of the New Social Movement, which emphasize collective participation, environmental sustainability, and community-based social change. The strategies implemented by BSI have resulted in increased public awareness and engagement in waste management. This study contributes to the development of more effective and sustainable community-based waste management policies and serves as a reference for waste bank programs in other regions.